Emile Petitot (1838-1916) - Savoie, Donat (ARCTIC, 1982)
. Emile Fortuné Stanislas Joseph Petitot entered the Congregation of the Oblate Missionaries of Mary-Immaculate in 1860. Fourteen days after his ordination, Petitot left France for the Mackenzie River, where he lived for the next twelve years, based at missions in Fort Providence, Fort Resolution, and principally Fort Good Hope. His accomplishments during his stay were remarkable. He collected material for his Dictionnaire de la langue Déné-dindjié, a dictionary of the major Athapaskan languages; Petitot's work still remains the best available in the field. Les Traditions indiennes du Canada Nord-Ouest records extensive legends from the Hare, Chipewyan, Loucheux, Dogrib, Cree, and Blackfoot cultures, all gathered during this period. Rarely at the missions, he travelled widely with native companions, often into territory completely unknown to both Petitot and his guides. . Attending to the physical, as well as spiritual, well-being of the Indians, Petitot nursed them when they were sick, and supplied them with necessary food and clothing. Although suffering from an abdominal rupture, he designed, decorated, and helped build the Good Hope Chapel, declared an official historic site in 1981. In June 1870 he journeyed from Fort MacPherson to Lapierre House in the face of strong resistance from the Protestants, who considered that territory as inviolably theirs. His maps of the vicinity of Great Slave Lake, of the Anderson River, and of the western branches of the Yukon are remarkably accurate. Travelling between the Mackenzie and Liard rivers, he charted the Petitot River, named in his honour. He corrected and completed the maps of his precursors, notably Sir John Franklin. The Rivière La Roncière-Le Noury, which Petitot discovered in 1868 and placed on the map in 1875, was later denied any existence. Over 30 years after Petitot's discovery, the mouth of a large river (the Hornaday) was found to empty into Darnley Bay east of the supposed mouth of Petitot's Roncière, although the river's course was not extensively ...